Estimation of technological value and chemical composition of selected common wheat cultivars (Triticum aestivum L.) - Anna Fraś; Magdalena Wiśniewska; Damian Gołębiewski (Plant Breeding and Seed Science, 2020)
The aim of the study was to estimate the technological value and chemical composition of new common wheat cultivars. The experimental material consisted of grain and flour obtained from 5 cultivars of common wheat, registered in 2017-2019, donated by Plant Breeding Strzelce - IHAR Group Ltd., Co., and harvested in years 2017-2018. The physical characteristics of the grain were determined: milling yield, falling number, gluten content, Zeleny sedimentation index as well as farinograph analysis and laboratory baking were performed. Furthermore, the content of grain nutrients and dietary fiber was determined. Significant differences between cultivars in terms of technological parameters and chemical composition have been demonstrated. The protein content in the grain was in the range of 13.3-15.2%, and the amount of gluten in the range of 28.6-36.8%. The cultivars were characterized by low alpha-amylase activity with an average falling number value 331s. The average water absorption of flour was 62.1%, and the volume of obtained bread was in the range 318-381cm3. The bread of best quality was obtained from the Wilejka cultivar, that was also the richest source of protein. The average dietary fiber content from two years of research was 10.8%, including 7.7% of non-starch polysaccharides (NSP), of which 5.8% of the insoluble fraction (I-NSP) and 1.9% of the soluble fraction (S-NSP). The richest source of dietary fiber was the spring wheat Alibi. The tested cultivars were characterized by high technological value and very good chemical composition and can be recommended for use in the food industry.